Models of thermal conduction and non-local transport of relevance to space physics with insights from laser–plasma theory - Arber, T. D.; Goffrey, T.; Ridgers, C. (Frontiers in Astronomy and Space Sciences, 2023)
Models of solar and space plasmas require an accurate model for thermal transport. The simplest such model is to assume that the fluid approach is valid and local transport models can be used. These local transport coefficients are derived under the assumption that the electron mean-free-path is "small" compared to the temperature scale-length. When this approximation breaks down non-local transport models or thermal flux-limiters must be used to maintain a physically realistic model. This article will review the background theory, how small is "small" for the mean-free-path and what options there are for including non-local transport within the fluid framework. Much of this recent work has been motivated by laser-plasma theory where mean-free-paths can be large and Spitzer-Harm is never used.